Methyltransferase 1 (OsMTS1) interacts with hydroxycinnamoyltransferase 1 (OsHCT1) and promotes heading by upregulating heading date 1 (Hd1) - Sohail, Amir (Plant science (Limerick), 2025)
Heading date determines the distribution and yield potentials of rice, and is an ideal target for crop improvement using CRISPR/Cas9 genome editing system. In this study, we reported the loss-of-function of Methyltransferase 1 (MTS1), which promotes heading in rice. Here, we constructed knockouts and overexpression transgenic plants of OsMTS1 in ZH8015 and Nipponbare (NIP) for the first time to validate its heading date function in rice subspecies Oryza sativa ssp. Indica and O. Sativa ssp. Japonica, respectively. The OsMTS1 knockouts in ZH8015 and NIP rice significantly promoted heading date under both natural short days (NSD) and natural long days (NLD) conditions, while the overexpression of OsMTS1 significantly delayed heading date in ZH8015 and NIP rice under both NSD and NLD conditions. Likewise, the complementation transgenic plants displayed late heading date phenotype. OsMTS1 repressed heading through up-regulating Heading date 1 (Hd1) and down-regulating Early heading date 1 (Ehd1) and Heading date 3a (Hd3a). The OsMTS1 protein interacted with OsHCT1 proteins using a yeast two-hybrid (Y2H) assay. The Y2H and overexpression confirmed that OsMTS1 interacted with OsHCT1, which delayed heading by 4.7 days under NLD. Taken together, CRISPR/Cas9, genetic complementation, and overexpression results validated that OsMTS1 represses heading in Indica and Japonica rice under both NLD and NSD conditions. These results demonstrated that OsMTS1 is a useful target for breeding early maturing rice varieties by CRISPR/Cas9 gene editing of the functional allele. •OsMTS1 promotes heading by up-regulating Hd1 and interaction with OsHCT1 in rice (Oryza sativa ssp. Indica and japonica) under long day (LD) and short day (SD) conditions.•Heading date determines the distribution and yield potentials of rice, and is an ideal target for crop improvement using CRISPR/Cas9 genome editing system.•In this study, we reported the loss-of-function of Methyltransferase 1 (MTS1), which promotes heading in rice. We constructed knockouts and overexpression transgenic plants of OsMTS1 in ZH8015 and NIP for the first time to validate its heading date function in rice subspecies Oryza sativa ssp. Indica and O. Sativa ssp. Japonica, respectively.•The OsMTS1 knockouts in ZH8015 and NIP rice significantly promoted heading date under both natural short days (NSD) and natural long days (NLD) conditions, while the overexpression of OsMTS1 significantly delayed heading date in ZH8015 and NIP rice under both NSD and NLD conditions. Likewise, the complementation transgenic plants displayed late heading date phenotype.•OsMTS1 repressed heading through up-regulating Heading date 1 (Hd1) and down-regulating Early heading date 1 (Ehd1) and Heading date 3a (Hd3a). The OsMTS1 protein interacted with OsHCT1 proteins using a yeast two-hybrid (Y2H) assay.•The Y2H and overexpression confirmed that OsMTS1 interacted with OsHCT1, which delayed heading by 4.7 days under NLD.•Taken together, CRISPR/Cas9, genetic complementation, and overexpression results validated that OsMTS1 represses heading in Indica and Japonica rice under both NLD and NSD conditions. These results demonstrated that OsMTS1 is a useful target for breeding early maturing rice varieties by CRISPR/Cas9 gene editing of the functional allele.